PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PT. PALMANCO INTI SAWIT - Desi Desi; Elisabet Tambunan (JURNAL MUTIARA MANAJEMEN, 2020)
This study aims to determine and analyze the effect of promotion and product quality on purchasing decisions at PT. Palmanco Inti Sawit. The formulation of the problem in the study was " The effect of promotion and product quality on purchasing decisions at PT. Palmanco Inti Sawit ". This research was conducted using descriptive analysis methods and statistical methods. The data used in this study are primary data and secondary data. The results of the study based on the partial t-test showed that promotion had an effect on purchasing decisions and product quality had an effect on purchasing decisions. By comparing the F count of 3.372 with the value of F table = 3.14, it means that the effectiveness of promotion and product has a significant effect on purchasing decisions. The coefficient of determination (adjusted R²) is 0.067. explained promotion and product quality, while the rest, namely 33 %%, purchasing decisions are explained by other variables such as price, location, etc.